CLINICAL COURSE OF BRONCHIAL ASTHMA IN CHILDREN WITH DIFFERENT DISEASE PHENOTYPES - Kukhtinova, Natalya Vladilenovna; Zelenskaya, Vera Victorovna; Kondyurina, Elena Gennadievna (Mother and Baby in Kuzbass, 2026)
The identification of asthma phenotypes is of critical importance in pediatric practice for selecting programs of primary and secondary prevention, as well as for choosing an appropriate treatment approach.The aim of the research – to identify potential differences in the clinical course of bronchial asthma in children depending on their atopic status.Materials and methods. A comparative analysis was conducted of the clinical course of the disease in 439 patients, divided into three groups: atopic bronchial asthma, non‑atopic asthma, and transient infantile obstruction. The assessment was based on the following characteristics: seasonality and frequency of exacerbations, volume of maintenance therapy required to achieve disease control, and quality of life.Results. The study revealed the following key differences:•    Atopic phenotype: exacerbations were associated with a specific season in 24 % of children (most commonly late spring and early summer).•    Non‑atopic phenotype: seasonality was less pronounced (only 13 % of cases), with the majority of exacerbations occurring during the autumn–winter period (80 %).•    Frequency of exacerbations: the mean number of exacerbations per year did not differ significantly: 5,1±0,74 in atopic patients and 4,8±0,98 in non‑atopic patients. However, among children with the non‑atopic phenotype, patients with fewer than 6 exacerbations per year were more common.•    Clinical manifestations: the groups did not differ in terms of the main clinical signs of exacerbation.•    Treatment for disease control: in patients without atopic markers, therapy with antileukotriene agents was sufficient in 38 % of cases.•    Pharmacotherapy requirements: children with atopic asthma required inhaled glucocorticosteroids twice as often (54 % vs. 33 %).•    Quality of life: children with non‑atopic asthma had a higher quality of life (PAQLQ: 3,9±0,4 points) compared to those with the atopic phenotype, in whom the disease had a greater impact on daily activities (PAQLQ: 6,1±0,6 points, p=0,002).Conclusions. The results of the study demonstrate the existence of distinct phenotypes of pediatric bronchial asthma. Further in‑depth study of these phenotypes may serve as the basis for personalized therapy and prevention strategies.
Keywords: children; bronchial asthma; phenotype; atopy; non‑atopic bronchial asthma; quality of life